2017
DOI: 10.1111/ahe.12289
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Cytochemical Characteristics of the Blood Cells of the Yellow-Bellied Slider (Trachemys scripta scripta)

Abstract: The increasing prevalence of yellow-bellied sliders (Trachemys scripta scripta) as pets in the European Union and also its utilization as animal models for experimental purposes makes crucial an accurate classification of their blood cells. The aim of this work was to provide a morphologic classification based on the cytochemical characteristics of the blood cells of 15 yellow-bellied sliders. Cytochemical stains included benzidine peroxidase, chloroacetate esterase, alpha-naphthyl butyrate esterase (with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
6
1
Order By: Relevance
“…Neutrophils are important phagocytes and they are also vitally important in the immune system ( Roos, Voetman & Meerhof, 1983 ). In this study, neutrophils were strongly positive for ACP, SBB, and positive for PAS and POX staining, this cytochemical pattern was similar to that described in human, some reptiles and amphibians ( Xu et al, 2005 ; Casal & Orós, 2007 ; Chansue et al, 2011 ; Cooper-Bailey et al, 2011 ; Bricker, Raskin & Densmore, 2012 ; Hernández et al, 2017 ). The strongly positive for ACP, SBB, and positive for PAS and POX staining indicated that tiger frog neutrophils may have a strong capability of phagocytosis and bactericidal effect.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Neutrophils are important phagocytes and they are also vitally important in the immune system ( Roos, Voetman & Meerhof, 1983 ). In this study, neutrophils were strongly positive for ACP, SBB, and positive for PAS and POX staining, this cytochemical pattern was similar to that described in human, some reptiles and amphibians ( Xu et al, 2005 ; Casal & Orós, 2007 ; Chansue et al, 2011 ; Cooper-Bailey et al, 2011 ; Bricker, Raskin & Densmore, 2012 ; Hernández et al, 2017 ). The strongly positive for ACP, SBB, and positive for PAS and POX staining indicated that tiger frog neutrophils may have a strong capability of phagocytosis and bactericidal effect.…”
Section: Discussionsupporting
confidence: 89%
“…However, there were great differences in their morphology. Mammalian platelets are enucleated and mostly round to oval disk-shaped ( Salakij et al, 2000 ; Prihirunkit et al, 2007 ; Techangamsuwan et al, 2010 ), while thrombocytes in lower vertebrates mostly present round, teardrop, fusiformis or spindle in shape, with a nucleus ( Salakij et al, 2002 ; Chansue et al, 2011 ; Bricker, Raskin & Densmore, 2012 ; Fang et al, 2014 ); The thrombocytes of the tiger frog mostly presented long rods or spindle in shape with clear edges and distinct boundaries between nucleoplasms, this morphological characteristics was in accord with that described in American bullfrog ( Bricker, Raskin & Densmore, 2012 ) and king cobra ( Ophiophagus hannah ) ( Salakij et al, 2002 ), but different from dubois’s tree frog ( Madhusmita & Kumari, 2014 ), yellow-bellied slider ( Trachemys scripta scripta ) ( Hernández et al, 2017 ) and captive bobtail lizard ( Tiliqua rugosa ) ( Moller, Gaál & Mills, 2016 ), whose thrombocytes often presented round or oval in shape.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations